Multifocal Infantile Hemangiomas Treated by Oral Itraconazole: A Case Report - Wei Wu; Sushmita Pradhan; Xin Ran; Yanxia Cai; Jinying Xie; Shunting Zhou; Yuping Ran (Nepal Journal of Dermatology, Venereology & Leprology)
We describe a case of a 2-month-old girl presented with more than 60 papules and nodules of hemangiomas involving the skin of the sclera, endocanthion, lower lip, and labium majus pudenda without visceral hemangiomas and laboratory abnormality. A skin biopsy showed numerous scattered, clearly limited, irregular cellular lobules in the dermis circumvoluted into capillaries comprising incomplete vessel walls, which was consistent with a diagnosis of multifocal cutaneous infantile hemangioma. Oral treatment with itraconazole (5mg/kg/day) for 26 weeks resulted in predominantly involution of the skin hemangiomas. We would like to report a rare case of multifocal cutaneous infantile hemangioma, successfully treated with oral itraconazole.